(untitled) (Journal of the College of Basic Education, 2022)
This study amis to establish reference range for thyroid hormons and thyroid stamulating hormon in normal healthy indeviduals of iraqi community concedering varied dietary habits and geographical differences in iraq . Three thousend samples of blood were collected by veinpuncture from healthy ideveduals aged between 20-50 years for both sex durig years 2000 to 2002 . the iraqi country was divided into three regions , north ( Mousel and Arbel ) , meddel ( Baghdad ) and south ( Basrah ) . Thyroid function tests include Triiodothyronine (T3) , Thyroxine (T4) and Thyroid stamulating hormon (TSH) , were examined using radioimmunoassy method (RIA) for both T3 and T4 whereas TSH was estimated using immunoradiomatric assay method (IRMA) . The results showed that combind femal and male normal range values for T4 and T3 was (2-12.47 μg/dl) and ( 0.24 -2.00 ng/ml) respectevely and the normal range value of TSH was ( 0.3-4.5μIU/ ml ) . levels of T3 , T4 and TSH under study were determined using SPSS statistically analysis. Our results of iraqi community normal ranges for (T3,T4,TSH) hormones were compared with that of the identical Amersham company values which showed a significant increase in the lower and higher limits for the thyroid hormones, while the TSH level only differe in the lower limits. On the bases of the results in this study , we conclud that normal range for lower and uper limits of our range are different from one reagion to another in our country . therefor determination of normal range for each region will provid important cotrabutions to the clinicans.